Bis(imino)aryl NCN pincer cobalt complexes: synthesis and disproportionation. Issue 16 (2nd April 2020) - Huang, Li-cheng; Zhang, Jing-shun; Jia, Teng; Mu, Ying; Gao, Wei
Abstract : Unexpected disproportionation was observed in the reaction of [NCN]Li with CoX2 . The disproportionation reaction was found to be dependent on the size of ortho groups in imine moieties of the ligands and the reaction conditions. Abstract : Treatment of iPr [NCN]Br (2, 6-(2, 6- i Pr2 C6 H3 CN)2 C6 H3 Br) with n BuLi in THF and the subsequent addition of 1 equiv. of CoCl2, CoCl2 (Ph3 P)2, and CoBr2 gave pincer Co(ii ) complexes { iPr [NCN]Co(μ-Cl)}2 (1d ), iPr [NCN]CoClPh3 P (1d -Ph3 P), and iPr [NCN]CoBr2 ·Li(THF)4 (1d -LiBr) respectively in moderate yields, whereas the slow addition of in situ prepared iPr [NCN]Li to CoCl2 in THF afforded an unexpected mixed-valence cobalt(i /ii ) complex κ 2 C, N, η 6-iPr [NCN]Co-κN -CoCl3 ·Li(THF)4 (2d ). Complex 2d was probably formed via a disproportionation reaction of the iPr [NCN]Co(ii ) species with excess CoCl2 during the reaction. Nevertheless, addition of CoCl2 to in situ formed 1d -THF at room temperature did not lead to 2d but gave a trinuclear Co(ii ) complex { iPr [NCN]Co(μ-Cl)(μ-Br/Cl)}2 Co (1d -CoCl2 ) in moderate yield. Similar reactions using ligands containing small ortho groups in the imine moieties R [NCN]Br (2, 6-(2, 6-Me2 C6 H3 CN)2 C6 H3 Br, Me [NCN]Br; 2, 6-(2, 6-Et2 C6 H3 CN)2 C6 H3 Br, Et [NCN]Br; 2, 6-(2, 4, 6-Me3 C6 H2 CN)2 C6 H3 Br, Mes [NCN]Br) and CoBr2, regardless of the reactant addition sequence, afforded mixed-valence cobalt(i /ii ) complexes {κ 2 C, N, η 6-R [NCN]Co-κN -CoBr(μ-Br)}2 ( Me [NCN] (2a ), Et [NCN] (2b ), and Mes [NCN] (2c )), suggesting that the bulkiness of the ortho -groups in the imine moieties of the ligands plays an important role in the disproportionation reaction. In the presence of PMe3, Co(ii ) complexes κ 2 C, N - R [NCN]CoBr(PMe3 )2 (3a–d ) and a bisligated cobalt(ii ) complex κ 3 N, C, N -κ 2 C, N - iPr [NCN]2 CoPMe3 (4d ) can be prepared respectively in high yields. The molecular structures of 1d -LiBr, 1d -CoCl2, 2b, 2d, 3a, and 4d were confirmed by X-ray crystallographic analysis and the detailed mechanisms of the disproportionation reaction were proposed.